Novel insights into the contribution of plastoglobules and reactive oxygen species to chromoplast differentiation. Issue 5 (5th December 2022) - Morelli, Luca; Torres‐Montilla, Salvador; Glauser, Gaétan; Shanmugabalaji, Venkatasalam; Kessler, Felix; Rodriguez‐Concepcion, Manuel
Summary: Plant tissues can be enriched in phytonutrients not only by stimulating their biosynthesis but also by providing appropriate sink structures for their sequestering and storage. In the case of carotenoids, they accumulate at high levels in chromoplasts naturally found in flowers and fruit. Chromoplasts can also be artificially differentiated from leaf chloroplasts by boosting carotenoid production with the bacterial protein crtB. Here we used electron and confocal microscopy together with subplastidial fractionation and transcript, protein and metabolite analyses to analyze the structural and biochemical changes occurring in crtB‐induced artificial chromoplasts and their impact on the accumulation of health‐related isoprenoids. We show that leaf chromoplasts develop plastoglobules (PG) harboring high levels of carotenoids (mainly phytoene and pro‐vitamin A β‐carotene) but also other nutritionally relevant isoprenoids, such as tocopherols (vitamin E) and phylloquinone (vitamin K1). Further promoting PG proliferation by exposure to intense (high) light resulted in a higher accumulation of these health‐related metabolites but also an acceleration of the chloroplast‐to‐chromoplast conversion. We further show that the production of reactive oxygen species (ROS) stimulates chromoplastogenesis. Our data suggest that carotenoid accumulation and ROS production are not just consequences but promoters of the chromoplast differentiation process. Abstract : See also the Commentary on this article by Lundquist, 237 : 1483–1485 .